Evaluation of lactate detection using selective multiple quantum coherence in phantoms and brain tumours. (14th January 2015) - Harris, L. M.; Tunariu, N.; Messiou, C.; Hughes, J.; Wallace, T.; DeSouza, N. M.; Leach, M. O.; Payne, G. S.
<x xml:space="preserve">Abstract</x> Lactate is a product of glucose metabolism. In tumour tissues, which exhibit enhanced glycolytic metabolism, lactate signals may be elevated, making lactate a potential useful tumour biomarker. Methods of lactate quantitation are complicated because of overlap between the lactate methyl doublet CH3 resonance and a lipid resonance at 1.3 ppm. This study presents the use of a selective homonuclear multiple quantum coherence transfer sequence (SelMQC‐CSI), at 1.5 T, to better quantify lactate in the presence of lipids. Work performed on phantoms showed good lactate detection (49%) and lipid suppression (98%) efficiencies. To evaluate the method in the brain, the sequence was tested on a group of 23 patients with treated brain tumours, either glioma (N = 20) or secondary metastases in the brain (N = 3). Here it was proved to be of use in determining lactate concentrations in vivo. Lactate was clearly seen in SelMQC spectra of glioma, even in the presence of lipids, with high grade glioma (7.3 ± 1.9 mM, mean ± standard deviation) having higher concentrations than low grade glioma (1.9 ± 1.5 mM, p = 0.048). Lactate was not seen in secondary metastases in the brain. SelMQC‐CSI is shown to be a useful technique for measuring lactate in tumours whose signals are otherwise contaminated by lipid. © 2015 The Authors NMR in Biomedicine Published by John Wiley & Sons Ltd.